Mapping for good change - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
In Kasika conservancy, on the East Chobe floodplain in northeastern Namibia, local people are using modern spatial information technologies to produce detailed maps...